Georg Simmel e as ambigüidades da modernidade - João Carlos Tedesco (Ciências Sociais Unisinos)
The text analyses some aspects of Simmel´s critical theory on the forms of modern sociability, their repercussions on the cultural horizon and some strategies adopted by individuals to face this process